2014
DOI: 10.1590/s1415-47572014000400002
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profile of fibroblasts obtained from the primary site, lymph node and bone marrow of breast cancer patients

Abstract: Cancer-associated fibroblasts (CAF) influence tumor development at primary as well as in metastatic sites, but there have been no direct comparisons of the transcriptional profiles of stromal cells from different tumor sites. In this study, we used customized cDNA microarrays to compare the gene expression profile of stromal cells from primary tumor (CAF, n = 4), lymph node metastasis (N+, n = 3) and bone marrow (BM, n = 4) obtained from breast cancer patients. Biological validation was done in another 16 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The transcriptomic signatures of CAF subsets from LN validated molecular similarities between CAF-S1 (or CAF-S4) from PT and LN. If few studies addressed CAF transcriptomic profiles in both PTs and LNs from BC patients 37,69 , a short gene list identified in ref. 37 allows to discriminate LN from PT bulk samples.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptomic signatures of CAF subsets from LN validated molecular similarities between CAF-S1 (or CAF-S4) from PT and LN. If few studies addressed CAF transcriptomic profiles in both PTs and LNs from BC patients 37,69 , a short gene list identified in ref. 37 allows to discriminate LN from PT bulk samples.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent reports indicate that CAFs are present at secondary tumor sites [46,47]. However, more studies are needed to better understand the roles of CAFs in metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their regular morphology, several studies have revealed that CAF have distinct mRNA and protein expression profiles that distinguish them from fibroblasts in adjacent normal breast tissue [4]. For example, they show increased expression of genes related to development and morphogenesis, such as NOTCH2 [4,26]. Additionally, a bidirectional signaling pathway between CAF and cancer cells suggests that CAF might influence the transcriptional profile of breast cancer cells [4].…”
Section: Components Of the Microenvironment And Their Interplay With mentioning
confidence: 99%